Effect of Ultrasonic, Microwave and Combined Microwave–Ultrasonic Pretreatment of Municipal Sludge on Anaerobic Digester Performance - Yeneneh, Anteneh; Chong, Siew; Sen, Tushar; Ang, Ha Ming; Kayaalp, A. (Springer Netherlands, 2013)
Anaerobic digestion is one of the most effective means for the stabilisation of sludge. However, it has a very slow rate-limiting hydrolysis phase which is attributed to the low biodegradability of cell walls and the presence of extracellular biopolymers. This study aims at investigating the effect of ultrasonic, microwave and combined microwave–ultrasonic treatment on biogas production, solids removal and dewaterability of anaerobically digested sludge. A comparison was made between the three pretreatment techniques conducting the digestion tests under similar conditions on the same synthetic sludge sample inoculated by digested sewage sludge. The experimental results depict that the combined microwave–ultrasonic treatment (2,450-MHz, 800-W and 3-min microwave treatment followed by 0.4-W/ml and 10-min ultrasonication) resulted in better digester performance than ultrasonic or microwave treatment. Mesophilic digestion of combined microwave–ultrasonic-pretreated sludge produced a significantly higher amount of methane (147 ml) after a sludge retention time of 17 days, whereas the ultrasonic- and microwave-treated sludge samples produced 30 and 16 ml of methane, respectively. The combined microwave–ultrasonic treatment resulted in total solids reduction of 56.8 % and volatile solid removal of 66.8 %. Furthermore, this combined treatment improved dewaterability of the digested sludge by reducing the capillary suction time (CST) down to 92 s, as compared to CST of 331 s for microwave-treated and 285 s for ultrasonically treated digested sludge samples. Optimisation tests were also carried out to determine the best combination.